Annual review article: Is it time to rethink the gender agenda in entrepreneurship research? - Marlow, Susan; Martinez Dy, M. (Sage, 2017)
This article develops a critique of contemporary approaches to analysing the impact of gender upon entrepreneurial propensity and activity. Since the 1990s, increasing attention has been afforded to the influence of gender upon women’s entrepreneurial behaviour; such analyses have highlighted an embedded masculinity within the entrepreneurial discourse which privileges men as normative entrepreneurial actors. Whilst invaluable in revealing a prevailing masculine bias within entrepreneurship, this critique is bounded by positioning women as a proxy for the gendered subject. This is a potentially limiting analysis that does not fully recognise gender as a human property with myriad articulations enacted throughout entrepreneurial activity. To progress debate, we engage more deeply with the notion of gender as a multiplicity exploring the implications of such for future studies of entrepreneurial activity.